Pelatihan Pembuatan Preparat Biologi sebagai Sarana Peningkatan Media Pembelajaran Bagi Guru-Guru Biologi di Kabupaten Bangka - Robika, Robika (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
One of the learning models with a scientific approach is the practicum method. In practical activities, students will carry out observation, experiment, and reasoning activities. A lot of knowledge about the phenomena that occur in living things that must be supported by direct observations and experiments. Therefore, this community service aims to provide skills to biology teachers in junior and senior high schools in terms of making biological preparations as a means of improving biology learning. The method used in facilitating the improvement of preparation skills by conducting training is through (1) the lecture method, namely providing the basic theory of making preparations and (2) the practical method, namely the participants carry out direct practice of making preparations using two methods namely whole mount and free hand-technic accompanied by a servant. . The results of the activity showed that the participants were able to make preparations well, marked by the results of the incision using two methods that were more than 70% observable. The results of measuring participant responses indicate that the majority stated that the methods used during the training could be applied in school